2022
DOI: 10.32764/schoolar.v2i1.1573
|View full text |Cite
|
Sign up to set email alerts
|

Quality in using Google Classroom as an Online Learning Media in Arabic Lesson

Abstract: This study aims to describe the quality of the use of Google Classroom as an online learning medium for Arabic subjects. This study uses descriptive qualitative research with an analytical approach to online learning using google classroom. The data in this study were obtained by means of interviews and distributing questionnaires on the quality of using google classroom as a learning medium. The results of observations also show that online learning using Google Classroom has a very good impact. With the feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…This blend allows for flexibility and continuous engagement. Research has shown that Google Classroom offers usability, accessibility, and benefits for both educators and students (Oladele et al, 2021;Susanto et al, 2021;Cahya & Ashoumi, 2022).…”
Section: Post-classmentioning
confidence: 99%
“…This blend allows for flexibility and continuous engagement. Research has shown that Google Classroom offers usability, accessibility, and benefits for both educators and students (Oladele et al, 2021;Susanto et al, 2021;Cahya & Ashoumi, 2022).…”
Section: Post-classmentioning
confidence: 99%
“…There are a variety of approaches that may be used to teach Arabic, but not all of them are appropriate for every topic. Lectures, PowerPoint presentations, class discussions, and student-teachers all seem to fall short of what's needed to get students engaged in their studies, especially in Arabic (Cahya & Ashoumi, 2022).…”
Section: Introductionmentioning
confidence: 99%